OP0061 Kineret® (Anakinra) Controls Disease Symptoms in Patients with Severe Cryopyrin-Associated Periodic Syndromes (CAPS): Up to 5-Year Follow-Up Data. (23rd January 2014) - Olivecrona, H.; Aldén Raboisson, M.; Söderberg, K.; Hallén, B.; Leinonen, M.; Sibley, C.; Plass, N.; Brewer, C.; King, K.; Zalewski, C.; Kim, J.; Bishop, R.; et al.
Abstract : Background: In severe forms of the rare monogenic autoinflammatory syndrome CAPS (NOMID, also denoted CINCA), persistent systemic and organ specific inflammation includes rash, central nervous system, and eye and cochlear inflammation leading to progressive hearing and vision loss. CAPS is caused by an uncontrolled IL-1β release, demonstrated by the often complete response after treatment with the IL-1 blocker anakinra (Kineret®) in all three entities of CAPS 1, 2, 3 Objectives: To characterize the long-term efficacy and safety of Kineret® in patients with severe CAPS. Methods: A prospective, open-label withdrawal design study with long-term extension including 43 patients (7 adult and 36 pediatric) was conducted at the NIH (study 03-AR-0298). Diary disease sum scores (DSSS), inflammatory serum markers, CNS inflammation, hearing, vision, joint status, quality of life, and safety were evaluated for up to 5 years, and the pharmacokinetics and dosing of Kineret® in CAPS patients were evaluated. Results: The median follow up time for the 43 patients was 4.9 years (range <0.1 to 5.4 years); 40 patients completed 3 or 6 months follow up and22/43 (51.2%) patients completed 60 months of treatment or more. Age at recruitment was 0.7 - 46.3 years (mean [SD] 10.3 [10.4]). Key symptoms (DSSS), decreased within 3 days of Kineret® initiation, from a mean baseline value of 4.5 to 0.8. At Month 3-6 (n=29), the estimated change was -3.5 (95% CI -3.7 to -3.3; p <0.0001). Median SAA and hsCRP levels decreased from 149 mg/L and 51 mg/L to 6 mg/L and 4 mg/L, respectively. Treatment withdrawal resulted in a clinical and laboratory relapse within a few days3. The DSSS and inflammatory serum marker improvement was sustained for up to 5 years of Kineret® treatment. Active inflammatory CNS disease (headache, MRI, and LP data) sustainably improved, and hearing and vision remained stable during treatment. The number of affected joints sustainably decreased, and bone mineral density gradually increased. The overall CHAQ score and other QoL assessments improved progressively over 5 years. The pharmacokinetics of Kineret® in CAPS patients was similar to that in RA patients. Body-weight adjusted dosage was a safe and effective approach for treatment of CAPS. Initial doses were optimized to maintain remission; the maintenance dose range at 5 years was 3.2-3.6 mg/kg. Conclusions: Kineret® treatment for up to 5 years in severe CAPS patients was safe and resulted in the control of disease symptoms, inflammatory markers, CNS inflammation, and stabilized organ function. Careful monitoring with rapid individual dosing adjustments is important to achieve optimal control of organ inflammation. References: Hawkins PN et al. N Engl J Med 2003;348:2583–4 Hoffman HM et al. Lancet 2004;364:1779–85. Goldbach-Mansky et al.N Engl J Med 2006;355:581–92. Sibley CH et al. Arthritis Rheum 2012;64:2375–2386. Disclosure of Interest: H. Olivecrona Employee of: Swedish Orphan Biovitrum AB, M. Aldén Raboisson Employee of: Swedish Orphan Biovitrum AB, K. Söderberg Employee of: Swedish Orphan Biovitrum AB, B. Hallén Employee of: Swedish Orphan Biovitrum AB, M. Leinonen Consultant for: Swedish Orphan Biovitrum AB, C. Sibley: None Declared, N. Plass: None Declared, C. Brewer: None Declared, K. King: None Declared, C. Zalewski: None Declared, J. Kim: None Declared, R. Bishop: None Declared, S. Hill: None Declared, S. Paul: None Declared, D. Stone: None Declared, D. Chapelle: None Declared, J. Butman: None Declared, R. Goldbach-Mansky Grant/research support from: Swedish Orphan Biovitrum AB, Regeneron, and Novartis